Calculation of absorption coefficients of InSb₁₋xBix solid solutions - Vyklyuk, J.I.; Deibuk, V.G.; Rarenko, I.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Using local empirical pseudopotential with spin-orbit interaction taking into account the electron band structure of InSb₁₋xBix in virtual crystal approximation is calculated. For binary compounds InSb and InBi characteristic gaps between energy bands in high symmetry points of Brillouin zone satisfactorily coincide with known experimental results. Temperature dependencies were calculated using the Brooks-Yu method. A satisfactory coincidence of the band structure of InSb₁₋xBix, temperature and concentration dependencies with experimental data let us to investigate e₁ and e₂ dielectrical functions taking into consideration the temperature using integral equations by Kramers-Kronig. Having used them we also calculated an absorption coefficient a both for binary compounds InSb, InBi and for the triple alloy InSb₁₋xBix. These results correlate well with experimental ones in the area of the fundamental absorption.